2020
DOI: 10.1111/jopr.13275
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Screw Channel Angulation on the Fracture Resistance of Zirconia Abutments: An In Vitro Study

Abstract: Purpose The aim of this study was to investigate the effect of implant screw channel angulation on the fracture resistance of zirconia abutments without artificial aging. Materials and Methods Ten implant replicas were embedded in a jig of autopolymerizing acrylic resin. Using a surveyor and a metallic platform, the implant replicas were mounted centrally and with an angulation of 30°. A maxillary left central incisor crown was fabricated from pattern resin and scanned. The digital design of a monolithic zirco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…The quality and risk of bias assessments for the three articles included in the review were carried out using the appraisal tool created by JBI SUMARI [ 19 , 23 ], and findings are presented in Table 1 and Table 2 . The study by Roehling et al [ 21 ] was deemed to have low bias, while articles from Scherrer et al [ 15 , 22 ] and Paolantoni et al [ 20 ] were found to have a high level of bias. The level of bias for each article was determined by the JBI SUMARI appraisal tool [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality and risk of bias assessments for the three articles included in the review were carried out using the appraisal tool created by JBI SUMARI [ 19 , 23 ], and findings are presented in Table 1 and Table 2 . The study by Roehling et al [ 21 ] was deemed to have low bias, while articles from Scherrer et al [ 15 , 22 ] and Paolantoni et al [ 20 ] were found to have a high level of bias. The level of bias for each article was determined by the JBI SUMARI appraisal tool [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Evolution in ceramic manufacturing technology has led to significant and predictable improvements in the characteristic of dental materials. Recently, the focus has shifted towards additive manufacturing techniques for fabrication of customized root-form zirconia implants utilizing a combination of stereolithography and digital light processing [ 15 , 30 ]. However, further in vitro and clinical research is essential to confirm its suitability for root-form dental implant manufacture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main concern regarding this fixation system is the reduced preload that can be applied to the retentive screw; this might lead to a higher rate of loosening of the restoration, especially in the posterior region [23]. Their application in zirconia abutments also showed a higher rate of abutment fracture [20].…”
Section: Discussionmentioning
confidence: 99%
“…ASCs can be applied to Porcelain Fused to Metal and, thanks to novel computeraided design and computer-aided manufacturing (CAD-CAM) systems, to Zirconia based restorations, both monolithic (completely made in zirconia, and then superficially colored [18]) and veneered (where a cutback is added in the design phase to provide space for subsequent veneering with ceramic [19]) [20].…”
Section: Introductionmentioning
confidence: 99%